TINJAUAN YURIDIS ORGANISASI SAYAP PARTAI POLITIK LOKAL DI ACEH - Jefrie Maulana; Djusfi, Apri Rotin; Aulia, Eza (Penerbit Universitas Atma Jaya Yogyakarta, 2023)
The existence of local political party wing organisations in Aceh has not yet received legal legitimacy. This creates legal uncertainty and injustice for local political parties in balancing national political parties so that special rules regarding local political party wing organisations must receive attention from the government. Further review through normative juridical studies by analysing aspects of legal certainty of the rights of local political parties in Aceh in the formation of party wing organisations and their driving factors. The formation of local political party wing organisations in Aceh in terms of statutory rules there is a legal vacuum, namely a situation where there are things that have not been regulated by law. This is in accordance with the adage het recht hink achter de feiten aan, i.e. the law always lags behind reality. Of course, this results in the absence of legal certainty for local political parties regarding the right to establish local political party wing organisations. The driving factor in the formation of local political party wing organisations in Aceh is the urgent need for local political parties to balance national political parties in facing unequal or unbalanced conditions in terms of external support in the form of political machines outside the party.